Komunikasi Ritual dan Nilai Filsafat Dalam Upacara Mapag Rare di Dusun Pemunut Kabupaten Lombok Barat - Kariana, I Nengah Putra (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2025)
This study examines the Mapag Rare ceremony conducted by the community of Pemunut Hamlet, West Lombok, as a form of ritual communication rich in symbolic meaning and local philosophical values. Using a descriptive qualitative approach, this research explores the communicative and philosophical dimensions embedded in each stage of the ritual, emphasizing how the community interprets the birth of a child as a spiritual event that connects humans with nature, ancestors, and the Divine. The findings reveal that communication during the ceremony occurs both verbally and non-verbally, through prayers, sacred water symbols, ketupat (rice cakes), yellow rice, and other ritual elements. Philosophical values such as purity, cosmic harmony, social solidarity, and submission to Divine will are strongly reflected in the practice. However, modernization poses challenges to the preservation of the ceremony’s philosophical meanings among younger generations. Therefore, a deep understanding of ritual communication and the values it embodies is essential to sustain the continuity of local cultural identity.